In vitro anticoagulant activities of Melastoma malabathricum Linn. aqueous leaf extract : a preliminary novel finding. - Manicam, Caroline; Abdullah, Janna Ong; Mohd Tohit, Eusni Rahayu; Seman, Zainina; Chin, Sieo Chin; Hamid, Muhajir (Academic Journals, 2010)
Limitations of existing anticoagulants have prompted a search for novel agents of natural origin.Fundamentals to this research was the observation that the aqueous leaf extract of Melastoma malabathricum Linn. possesses potent anticoagulant property.In vitro coagulation assays such as activated partial thromboplastin time (aPTT), prothrombin time (PT) thrombin time (TT) and mixing studies were performed on citrated plasmas of healthy volunteer donors spiked with different concentrations of the leaf exact (100-1000μg/ml).The results showed that aPTT of plasma samples spiked with extract was markedly prolonged in a concentration-dependent manner (p<0.001), but was otherwise for PT and TT. Both types of mixing studies corrected the initially prolonged aPTT to normal range.The extract exhibited no inter-gender variability in its anticoagulant activity.This study highlights that the anticoagulant activity of M. malabathricumaqueous leaf extract affects the intrinsic pathway of the coagulation cascade by causing clotting factor(s) deficiency.